A Preliminary Theory of Interorganizational Network Effectiveness: A Comparative Study of Four Community Mental Health Systems - Provan, Keith G.; Milward, H. Brinton (Administrative Science Quarterly, 1995)
Keith G. Provan, H. Brinton Milward, A Preliminary Theory of Interorganizational Network Effectiveness: A Comparative Study of Four Community Mental Health Systems, Administrative Science Quarterly, Vol. 40, No. 1 (Mar., 1995), pp. 1-33